Pengembangan Buku Saku Berbasis Mind Mapping pada Pembelajaran PPKn Kelas III SD - Putri, Sintiya Arentika; Idris, Muhamad; Aryaningrum, Kiki (Indonesian Research Journal on Education, 2023)
This research and development aims to produce a product in the from of a mind mapping-basedpocket book in Civics learning for class III SD. There are problems found, namely teachers do not have teaching resources that innovate, still use the lecture method, and there are still students who have not reached the KKM value that has been set by the school. This research and develompment uses the Research and Development method using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects in this study were third grade students of SD Negeri 32 Palembang. Date collection instruments in the form of questionnaires and documentation. Date analysis in this study is to obtain validity and practicality. This research and development resulted in a valid pocket book used, with a score of 84% in the “Very Valid” caregory. It can be concluded that mind mapping-based pocket book teaching materials are suitable for uses in Civisc learning.